2004
DOI: 10.1177/1534734604272245
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Treatment for Varicose Veins: A Review of Endovenous Laser Treatment and Radiofrequency Ablation

Abstract: Varicose veins are a common problem, conventionally treated by an operation. Within the last few years, minimally invasive techniques have been developed as alternatives to surgery in an attempt to reduce morbidity and improve recovery time. Radiofrequency ablation and endovenous laser ablation are the most promising of these new techniques. This review article looks at the evidence for these techniques and the clinical experience to date and discusses their role in the future treatment of varicose veins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Most studies describing EVLA had used either 810-or 940-nm diode lasers based on a haemoglobin absorption peak to red/infrared light of 800-1000 nm. 22 The heat generated by the laser was believed to result in thermal damage to the endothelium and subendothelial layer, resulting in focal coagulative necrosis and shrinkage and leading to thrombotic occlusion of the vein. 23 However, histological studies at 3 and 6 months following EVLA indicate failure of endothelial regeneration and progressive damage to the muscle layers of the vein wall, resulting in further shrinkage and occlusion.…”
Section: Endovenous Laser Ablationmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies describing EVLA had used either 810-or 940-nm diode lasers based on a haemoglobin absorption peak to red/infrared light of 800-1000 nm. 22 The heat generated by the laser was believed to result in thermal damage to the endothelium and subendothelial layer, resulting in focal coagulative necrosis and shrinkage and leading to thrombotic occlusion of the vein. 23 However, histological studies at 3 and 6 months following EVLA indicate failure of endothelial regeneration and progressive damage to the muscle layers of the vein wall, resulting in further shrinkage and occlusion.…”
Section: Endovenous Laser Ablationmentioning
confidence: 99%
“…24 Studies had shown that between 30% and 99% of patients receiving EVLA require subsequent treatment for non-trunk varicosities. 22 It had been shown that successful occlusion was dependent on the energy used and could be achieved in all veins treated with ≥ 70 J/cm. 25 A RCT carried out by one of the CLASS co-investigators reported on 118 patients randomised to EVLA or surgery.…”
Section: Endovenous Laser Ablationmentioning
confidence: 99%
“…Endovenous laser treatment (ELT) is one of the most promising of these new techniques [2][3][4]. In 1999, Boné [5] first reported the delivery of endoluminal laser energy.…”
Section: Introductionmentioning
confidence: 99%
“…However, the percutaneous treatments described here are gaining momentum as a less invasive alternative when compared to SEPS. These treatments offer several advantages in that they can be applied with local anesthesia or oral/IV sedation, and distal perforators around the malleolus are easily treatable unlike SEPS (24,32,44). These treatments are performed without incisions, and are easily repeatable if necessary.…”
Section: Evtamentioning
confidence: 99%
“…Local side effects include ecchymosis, induration or paraesthesia. Rare systemic complications include DVT and pulmonary emboli (6,32,33). For laser energy, commercially available 940-nm diode, 1,320 nm Nd:YAG and 1,470-nm microfibers can be used for perforator vein ablation (34)(35)(36)(37).…”
Section: Evtamentioning
confidence: 99%